The Exon 3-Deleted/Full-Length Growth Hormone Receptor Polymorphism and Response to Growth Hormone Therapy in Growth Hormone Deficiency and Turner Syndrome: A Multicenter Study - BEREKET, ABDULLAH; DEMİRCİOĞLU, SERAP (KARGER, 2012)
Background/Aim: The exon 3-deleted/full-length (d3/fl) growth hormone (GH) receptor (GHR) polymorphism has been associated with responsiveness to GH therapy in some diagnostic groups. However, there are still controversies on this issue. To evaluate the effect of the GHR exon 3 polymorphism on growth after 1 and 2 years of GH therapy in Turkish patients with GH deficiency (GHD) and Turner's syndrome (TS) and the distribution of GHR exon 3 isoforms. Materials and Methods: 218 patients with GHD (125 males/93 females) and 43 patients with TS were included in the study. The control group included 477 healthy adults aged from 18 to 57 years (54 females/423 males). Anthropometric parameters and insulin-like growth factor (IGF)-1 and IGF binding protein (IGFBP)-3 were evaluated annually. GHR isoforms were studied using simple multiplex PCR. Height and body mass index were expressed as standard deviation score (SDS). Results: There were no differences among TS, GHD and healthy adults regarding the distribution of GHR exon 3 isoforms (fl/fl, fl/d3 and d3/d3). There was a significant increase in height SDS in both diagnostic groups on GH therapy; however, there were neither differences in height SDS and Delta height velocity between fl/fl, fl/d3 and d3/d3 groups nor a correlation between the distribution of GHR exon 3 isoforms and change in IGF-1 SDS and IGFBP-3 SDS levels on GH therapy in either of the diagnostic groups. There was also no gender difference in GHR isoforms in healthy adults. Conclusion: The results suggest that responsiveness to GH therapy does not depend on the exon 3 GHR genotypes in GHD and TS patients. Copyright (C) 2012 S. Karger AG, Basel
Keywords: Exon 3 polymorphism; Growth hormone receptor; Hormone deficiency; Human growth hormone; Therapy responsiveness; Turner syndrome; GESTATIONAL-AGE CHILDREN; WEIGHT HEIGHT VELOCITY; GH RECEPTOR; INCREASED RESPONSIVENESS; TURKISH CHILDREN; PUBERTAL CHANGES; FINAL HEIGHT; DELETION; GENE; STANDARDS